Pogled ZGS na nadaljnji razvoj javne gozdarske službe - Jakša, Jošt (Gozdarski vestnik, 2009)
The article talks about the significance of forming an integrative public forestry service for directing the forest management and forestry profession development in Slovenia. It describes the already realized work of the Slovenian Forestry Service and, by alleging the objectives and orientations from the National Forest Program and orientations from the internal developmental document - Development Strategy of the SFS, indicates its further development.
Keywords: forestry; gozdarstvo; Zavod za gozdove Slovenije; javne službe; Slovenia; Slovenija